Diagnosis and management of ductal carcinoma in situ (DCIS). - Virnig, Beth A (Evid Rep Technol Assess (Full Rep), 2009)
OBJECTIVES: Systematic synthesis of the published evidence about incidence, risk factors, and management options for women with ductal carcinoma in situ (DCIS) of the breast. DATA SOURCES: Original epidemiologic studies were sought from several databases to identity articles published in English between 1970 and January 31, 2009. REVIEW METHODS: Incidence of DCIS in the general population and among women at greater risk of breast cancer and patient outcomes after diagnostic magnetic resonance imaging (MRI) or sentinel lymph node biopsy (SLNB) were abstracted into the developed standardized form. Patient outcomes after breast conserving surgery with or without adjuvant radio- or chemotherapy or after mastectomy were compared from randomized controlled clinical trials (RCTs) and observational studies. RESULTS: Three hundred seventy-four publications were eligible for the review. Rarely diagnosed before 1980, the incidence of DCIS increased by 270 percent since 1987 to 37.5 per 100,000 women in 2001, partially due to increased use of mammography with no good evidence of overdiagnosis (63 publications). Incidence was higher with increasing age, breast density, and family history and lower among physically active women and aspirin users (29 publications). Tamoxifen did not prevent DCIS at longer followup in women at high risk of breast cancer (two RCTs). No good evidence was identified around the optimal use of MRI for treatment planning (64 publications). Case-series from academic centers reported that around 5 percent of women with final histological diagnosis of DCIS had positive sentinel nodes and 1 percent were upgraded to metastatic cancer with no significant differences in outcomes (50 publications). Good evidence from five RCTs (ten publications) suggested that breast conserving surgery with adjuvant radiation reduced ipsilateral (the same breast) tumors by 53 percent with no differences in mortality or contralateral (the second breast) cancer. One RCT demonstrated that adjuvant chemotherapy reduced ipsilateral and contralateral cancer. Ten-year post diagnostic survival was more than 98 percent, while the rates of ipsilateral cancer were around 10 percent (133 publications of 64 observational studies). Major risk factors for ipsilateral cancer were younger age, larger tumor size, comedo necrosis, and positive surgical margins. Limited evidence of worse incidence and advanced outcomes in racial subgroups varied across the studies. Inconsistent evidence suggested that Her2 receptor and negative estrogen receptor status were associated with worse outcomes. No good evidence was found that adjuvant chemotherapy or mastectomy can improve outcomes and there was no evidence on natural history of DCIS or on quality of life among women treated for DCIS. CONCLUSIONS: Incidence of DCIS continued to increase with no evidence of overdiagnosis or effective preventive strategies. There is a need to better identify problematic lesions from mammography that are most likely to contain some invasive breast cancer. Most prognostic factors for invasive breast cancer are also prognostic factors for DCIS. The role of MRI and SLNB should be investigated as tools to improve pre-surgical decisonmaking and staging. Breast conserving surgery with adjuvant radiotherapy can benefit all women, though the absolute impact may be small for some women. Ongoing trials will shed light on the optimal clinical strategy for treating DCIS.